Comparison of the Antibacterial Properties of Essential Oils of Malva Sylvestris and Salvia Officinalis on Common Bacteria of Oral Infection with Chlorhexidine Mouthwash - Hojjat Eghbal; Arezou Mohammadi; Nima Mohammad Nejad Khiavi; Mehdi Ahmadi Sabegh; Neda Jahani (Mashhad University of Medical Sciences, 2021)
Introduction: Malva sylvestris is one of the most important plants used in pharmaceutical, cosmetic, and health industries in most developing countries and has antiseptic properties. Salvia officinalis is an herbaceous plant belonging to the family of Lamiaceae (Labiatae) and one of the most important herbal plants used as a disinfectant in traditional and modern medicine. Therefore, this research aimed to evaluate essential oil components of Malva sylvestris and Salvia officinalis collected from Meshgin Shahr Ardabil Province, Iran, and their anti-bacterial properties on common bacteria of oral infection, compared to chlorhexidine mouthwash. Materials and Methods: In this research, Malva sylvestris and Salvia officinalis were collected from the Anzan region, Meshgin Shahr, northwest of Iran. The essential oil was extracted by Clevenger apparatus, and gas chromatography and gas chromatography-mass spectrometry devices were used to analyze essential oil compounds and accurately measure the compounds. Afterward, the effect of the essential oil of these plants on the common bacteria of the oral infection was evaluated through disc diffusion and minimum inhibitory concentration. Data were analyzed using analysis of variance (ANOVA). Results: According to the results, the essential oils of Malva sylvestris and Salvia officinalis had significant inhibitory effects on different types of gram-negative and -positive bacteria. The comparison of the mean growth inhibition zone of these plants' essential oils with chlorhexidine showed that the antibacterial property of the plants' essential oil mixture on Streptococcus mutans was higher than that of chlorhexidine mouthwash, which was significantly different. On the other hand, a relative increase in the diameter means of the growth inhibition zone was observed by plants' essential oils mixture on Klebsiella pneumoniae, compared to chlorhexidine mouthwash, which was not significantly different (p < 0.05). Moreover, it was found that the essence of these herbs showed relatively similar results to that of chlorhexidine. Conclusion: According to the findings, the essential oil of Malva sylvestris and Salvia officinalis had a good anti-microbial effect against the common bacteria of oral infections. As a result, the mixture of essential oil of these plants with different concentrations, after performing more comprehensive studies, can be an appropriate alternative for chemical drugs and chemical mouthwashes in the treatment of oral bacterial infections.